HUBUNGAN KOMPLEMENTER ANTARA MANAJEMEN PUNCAK PEREMPUAN DAN LITERASI KEUANGAN TERHADAP EARNINGS MANAGEMENT PADA PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2015 - Brenda Astrid Tamara; Yie Ke Feliana (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2019)
The purpose of this study is to examine whether the presence of female top management and female top management with financial literacy has an impact on reducing earnings management. Earnings management is proxied by discretionary accruals and measured using the Modified Jones (1995) model on a cross-sectional version. The study population use all company that has been listed in Bursa Efek Indonesia (BEI) at 2015. The amount of company used in this study are 291 companies. The results of this study shows that there is no effect between female top management and female top management with financial literacy on the reduction of earnings management.